2018
DOI: 10.3390/v10100550
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Consequences of Zika Virus Infection and Differential Impact on Neural Development

Abstract: Maternal infection with Zika virus (ZIKV) during pregnancy can result in neonatal abnormalities, including neurological dysfunction and microcephaly. Experimental models of congenital Zika syndrome identified neural progenitor cells as a target of viral infection. Neural progenitor cells are responsible for populating the developing central nervous system with neurons and glia. Neural progenitor dysfunction can lead to severe birth defects, namely, lissencephaly, microcephaly, and cognitive deficits. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 56 publications
(81 reference statements)
6
31
0
1
Order By: Relevance
“…Initial studies examining gene dysregulation following ZIKV infection were undertaken in human neural stem cells (hNSCs) [30,31], human neural progenitor cells (hNPs) [27,32], organotypic cultures [29,33], neurospheres [34], and cerebral organoids [35]. These studies used different ZIKV strains, multiplicities of infection, and lengths of infection, and thus the extent of ZIKV infection ranged from 2.5% to 90% [27,[29][30][31][32][33][34][35]. Consistent with earlier reports of ZIKV infection in SH-SY5Y cells [80,81], immunofluorescence analyses revealed that 40% of cells were infected (Figure 1a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies examining gene dysregulation following ZIKV infection were undertaken in human neural stem cells (hNSCs) [30,31], human neural progenitor cells (hNPs) [27,32], organotypic cultures [29,33], neurospheres [34], and cerebral organoids [35]. These studies used different ZIKV strains, multiplicities of infection, and lengths of infection, and thus the extent of ZIKV infection ranged from 2.5% to 90% [27,[29][30][31][32][33][34][35]. Consistent with earlier reports of ZIKV infection in SH-SY5Y cells [80,81], immunofluorescence analyses revealed that 40% of cells were infected (Figure 1a,b).…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental aspect of adult neurogenesis is the ability of NPCs to migrate great distances through the parenchyma to reach damaged areas of the brain (19). Neurotropic viruses, such as HIV, human cytomegalovirus (HCMV), and Zika virus (20)(21)(22)(23), are known to alter migration behavior of NPCs, but the effect of HSV-1 on NPC migration is unknown. To investigate the effect of HSV-1 on NPC migration and whether HSV-1-induced alteration of NPC migration can be prevented by antiviral treatment, NPCs were infected at MOIs of 0.1 to 0.001 in the presence of 5BVdU-IFN-␣.…”
Section: Resultsmentioning
confidence: 99%
“…In these cells, ZIKV infection is followed by apoptosis, corroborating the hypothesis of ZIKV as the etiological agent of these neurological disorders [4,5,[10][11][12]. Further, independent studies have shown that the microcephaly and neural development-associated phenotypes is not a distinct feature of the Asian lineage [12][13][14][15][16]. However, the precise molecular mechanism(s) underlying these ZIKV-related manifestations is not understood.…”
Section: Introductionmentioning
confidence: 68%